2023
DOI: 10.1007/s40477-023-00800-9
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of sonographic parameters for inflammatory bowel disease in children

Abstract: Purpose Intestinal ultrasound (IUS) is widely used as the first exam in patients with suspected inflammatory bowel disease (IBD). This study investigated the accuracy of several IUS parameters, including increased bowel wall thickening (BWT), in detecting IBD in a paediatric population. Methods The study included an unselected series of 113 patients aged 2–18 years (mean age 10.8 years, 65 male), referred for recurrent abdominal pain or altered bowel habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…That means that the examination can be performed by different doctors, with reproducibility, making it possible to compare results between observers and between time points, thus reducing subjectivity and increasing accuracy. The article also demonstrated that the correlation between color Doppler ultrasound of the intestinal wall and the fecal calprotectin level shows high sensitivity and specificity for identifying inflammatory activity in pediatric IBD, corroborating data in the literature (1) .…”
supporting
confidence: 83%
See 2 more Smart Citations
“…That means that the examination can be performed by different doctors, with reproducibility, making it possible to compare results between observers and between time points, thus reducing subjectivity and increasing accuracy. The article also demonstrated that the correlation between color Doppler ultrasound of the intestinal wall and the fecal calprotectin level shows high sensitivity and specificity for identifying inflammatory activity in pediatric IBD, corroborating data in the literature (1) .…”
supporting
confidence: 83%
“…Inflammatory bowel diseases (IBDs) comprise a group of diseases that cause chronic inflammation of the intestine, including Crohn's disease, ulcerative colitis, and inflammatory bowel disease unclassified. The incidence and prevalence of IBDs have increased over the last 50 years, with an incidence of 25% in the pediatric population, being more aggressive in this age group (1) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The particularities of the inflammatory reaction increase the relevance of altered bowel pattern, mesenteric fat hypertrophy and lymph node enlargement in children. However, these findings are highly non-specific, and their presence alone should not be considered an absolute diagnostic marker [37,40]. Radiological remission in this group has also been suggested to greatly reduce the risk of recurrence or complications [52,105].…”
Section: Discussionmentioning
confidence: 99%